Sotagliflozin in Patients with Diabetes and Chronic Kidney Disease - Bhatt, Deepak L; Szarek, Michael; Pitt, Bertram; Cannon, Christopher P; Leiter, Lawrence A; McGuire, Darren K; Lewis, Julia B; Riddle, Matthew C; Inzucchi, Silvio E; Kosiborod, Mikhail N; Cherney, David Z.I; Dwyer, Jamie P; et al. (The New England journal of medicine, 2021)
In a trial involving 10,584 patients with diabetes and chronic kidney disease, sotagliflozin resulted in fewer total deaths from cardiovascular causes, hospitalizations for heart failure, and urgent visits for heart failure than placebo. Diarrhea, mycotic infections, and diabetic ketoacidosis occurred with sotagliflozin.